(untitled) (Journal of Mining and Metallurgy, Section B: Metallurgy, 2023)
The present paper analyzes the effect of low aluminum additions and the hot forging process on the microstructure and non-metallic inclusions of high manganese steels. Four high-manganese steels (HMnS) were obtained by adding low aluminum contents of 1.1 and 1.5 wt. % in four medium carbon austenitic steels (0.3 - 0.4 wt. % C) with manganese contents of 17 and 22 wt. Samples of the as-cast steels were hot forged to 1100 °C to obtain a whole reduction of 70 %. The microstructural evolution was studied by microscopy techniques (OM, and SEM-EDS) and X-Ray diffraction measurements for the as-cast and hot forged steels. A typical grain columnar zone obtained during solidification of an ingot casting was obtained in the as-cast condition where the microstructure was constituted by non-metallic inclusions in a fully austenitic matrix. The non-metallic inclusions were identified as Al2O3 and MnS particles. The thermomechanical treatment allows the formation of an austenitic microstructure characterized by twins in high manganese steels while a duplex austenitic-martensitic microstructure was obtained for HMnS which contained the lowest manganese contents. The highest tensile properties were obtained for the steel 17Mn-1Al which showed the lowest grain size and finer non-metallic inclusions content. The hardness values were similar to those obtained in the as-cast condition.